2011
DOI: 10.1158/0008-5472.sabcs11-p5-18-05
|View full text |Cite
|
Sign up to set email alerts
|

P5-18-05: Incidence of Febrile Neutropenia in Patients Treated with Docetaxel and Cyclophosphamide (TC) for Adjuvant Breast Cancer.

Abstract: Background: Adjuvant docetaxel with cyclophosphamide (TC) chemotherapy use in the community is common based on its improved disease outcomes compared to doxorubicin with cyclophosphamide (AC) treatment, lack of cardiac toxicity associated with anthracyclines, and perceived low incidence of febrile neutropenia (FN). In the pivotal trial of AC versus TC, the incidence of FN in breast cancer patients who received TC treatment was 4% in patients under 65 years and 8% in patients greater than 65 years. Growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…More recently, in the first cycle only, the fn incidence in that trial was reported to be 2.8% with primary prophylaxis, which increased to 9.5% without it 10 . Our data are consistent with those from another report 11 that showed a significant difference in the rate of fn with (8.6%) or without (24.5%) primary prophylaxis during adjuvant tc chemotherapy. Finally, a recent meta-analysis 12 looking at 902 patients treated with tc chemotherapy estimated the fn rate to be 29% without primary prophylaxis.…”
Section: Discussionsupporting
confidence: 93%
“…More recently, in the first cycle only, the fn incidence in that trial was reported to be 2.8% with primary prophylaxis, which increased to 9.5% without it 10 . Our data are consistent with those from another report 11 that showed a significant difference in the rate of fn with (8.6%) or without (24.5%) primary prophylaxis during adjuvant tc chemotherapy. Finally, a recent meta-analysis 12 looking at 902 patients treated with tc chemotherapy estimated the fn rate to be 29% without primary prophylaxis.…”
Section: Discussionsupporting
confidence: 93%
“…TC is a common adjuvant chemotherapy protocol used for management of early breast cancer. The reported incidence of neutropenic fever in the largest randomised trial for this regimen is 5% and 9.5% in the first cycle without primary GCSF prophylaxis . One of the largest series of this protocol from Canada with 134 patients reported 38% incidence of neutropenic fever without primary prophylaxis similar to our study .…”
supporting
confidence: 83%
“…The updated result of this study reported a neutropenic fever rate of 5% . Many recent studies from the real‐world practice have shown a very high neutropenia rate with this protocol . A recent meta‐analysis confirmed that the risk of neutropenic fever is >20% with this regimen and upfront prophylaxis with colony‐stimulating factors may be recommended with this protocol .…”
mentioning
confidence: 53%
“…In a review, Weycker et al 6 reported rates of febrile neutropenia between 8.8% and 10.6%, albeit in settings where more than 50% of patients received G-CSF as primary prophylaxis. Many other series 7,8 Febrile neutropenia rates were higher (11.5%) than what was seen in TROPIC trial (8%) despite use of G-CSF as primary prophylaxis in 47% of patients. 10 However, a subsequent trial comparing 20 with 25 mg/m 2 showed non-inferiority with less toxicity.…”
Section: Introductionmentioning
confidence: 87%